Effects of intra- and inter-regional geographic diversification and product diversification on export performance: Evidence from the Chilean fresh fruit export sector. (July 2019) - Losilla Solano, Luis Vinicio; Brümmer, Bernhard; Engler, Alejandra; Otter, Verena
Highlights: Intra-regional diversification has an inverted U-shaped relationship with performance. Inter-regional diversification has an inverted U-shaped relationship with performance. Product diversification has a positive effect on performance. Product diversification negatively moderates inter-regional diversification performance. Product diversification does not moderate intra-regional diversification performance. Abstract: This study examines individually the effects of intra- and inter-regional geographic diversification on the export performance of firms from the Chilean fresh fruit sector. It also explores the direct effect of related product diversification on export performance and its role as a moderator in the relationship between geographic diversification and export performance. By employing panel trade data of 279 purely exporting firms over a six-years period (2010–2015), we found that both intra- and inter-regional diversification have an inverted U-shaped relationship with export performance, where moderate levels of diversification have positive effects on export performance, but higher levels may be counterproductive. Results also showed that related product diversification has a positive effect on firm export performance and a negative moderating effect on the relationship between inter-regional diversification and export performance. In the case of intra-regional diversification, we did not find any moderating effect from product diversification. By focusing on firms from the agricultural sector based in an emerging economy, this study offers practical implications for firm managers, trade organizations and private export associations, that may also be applicable to other export-based activities and emerging economies.